2024
DOI: 10.1088/1755-1315/1292/1/012026
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of certification on perceived product quality of livestock food products

S P Syahlani,
A Triatmojo,
N M A K Dewi

Abstract: Product safety in the livestock food product industry needs to control several factors that potentially cause health problems. Product certification regulation becomes one of the important requirements to ensure that offering livestock products is safe for consumers. This study aims to investigate the effect of product certification implemented in Indonesia for livestock food products that were MD, Halal, Organic, and NKV on the perceived product quality of fresh and processed livestock food products. This exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…NKV certificates were only taken into account by 14.28% of respondents, while MD BPOM (Makanan Dalam, issued by Badan Pengawas Obat dan Makanan Republik Indonesia or BPOM RI (The Indonesian Food and Drug Authority and Halal certificates, both of which are considered by the majority of respondents, that is, 91.43% and 87.62% respectively (Table 4). Prior study showed that NKV certification of livestock processed food products is less likely to increase perceived product value compared to Halal certification (Syahlani et al, 2024b). It can't be denied that currently, NKV certificates are still widely considered for purchasing decisions, therefore government needs to disseminate information and educate consumers about the importance of NKV certification.…”
Section: Resultsmentioning
confidence: 99%
“…NKV certificates were only taken into account by 14.28% of respondents, while MD BPOM (Makanan Dalam, issued by Badan Pengawas Obat dan Makanan Republik Indonesia or BPOM RI (The Indonesian Food and Drug Authority and Halal certificates, both of which are considered by the majority of respondents, that is, 91.43% and 87.62% respectively (Table 4). Prior study showed that NKV certification of livestock processed food products is less likely to increase perceived product value compared to Halal certification (Syahlani et al, 2024b). It can't be denied that currently, NKV certificates are still widely considered for purchasing decisions, therefore government needs to disseminate information and educate consumers about the importance of NKV certification.…”
Section: Resultsmentioning
confidence: 99%